Application of an automated protocol for the analysis of the temporal parameters of the response of reaction tennis players during the execution of split-step and volley - R. Menayo; J.P. Fuentes; V. Luis; F. J. Moreno (Asociación Española de Ciencias del Deporte, 2010)
This study is aimed to show the design and application process of an automated system to recording in real time the temporary parameters of tennis players reaction response during the execution of the technical-tactical movement called "split-step and second volley". The knowledge about temporary characteristics of the action will be make used of identify the variables to cause in that and also to design an investigation to permit an improvement of the tennis players efficiency in this sequence of the play. In this way, the use of the technological system will allow a precise analysis of player's motor response and the eminent information about the defined action KEY WORDS: Tennis, split-step and volley, automated system of measure, reaction response